Regucalcin is an androgen-target gene in the rat prostate modulating cell-cycle and apoptotic pathways - Vaz, C V (2019)
Regucalcin (RGN) is a calcium (Ca(2+) )-binding protein underexpressed in prostate adenocarcinoma comparatively to non-neoplastic prostate or benign prostate hyperplasia cases. Moreover, RGN expression is negatively associated with the cellular differentiation of prostate adenocarcinoma, suggesting that loss of RGN may be associated with tumor onset and progression. However, the RGN actions over the control of prostate cell growth have not been investigated.